A multiband flexible terahertz metamaterial with curvature sensing functionality. (18th May 2016) - Zhao, Xiaoqing; Yang, Bin; Liu, Jingquan; Pitchappa, Prakash; Hasan, Dihan; Ho, Chong Pei; Yang, Chunsheng; Lee, Chengkuo
Abstract: In this paper, we present a multiband flexible metamaterial in which one resonance acts as a strain sensor, while the others remain unchanged with bending strain, which might occur due to wrapping around an irregular curved surface. From both experiment and simulation, four transmission dips were observed at around 0.51, 1.34, 1.72 and 1.81 THz, respectively. The results indicated that the resonance dips in the flexible metamaterial arose from the different orders of dipole resonance mode. In the experiment, the frequency shift and amplitude modulation of the transmission at the first resonance increased linearly with the increase of the relative length change Δ l / L and changed as an exponential function of the applied bending strain. In addition, the first resonance frequency of the horizontal dipole blue shifted by 6.4 GHz, or about 1.29%, while the relative intensity change of 31.95% in the transmission was achieved when the strain was 2.79‰. This study promises applications in curvature sensing and other controllable metamaterial-based devices.